2020
DOI: 10.31219/osf.io/85gwy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generating Seizure-Inducing Sequences with Interactive Visualizations

Abstract: Interactive visualizations are often built to draw the eye towards pertinent information with attention-grabbing pops of color and patterns. These techniques, though helpful in engaging the average user and nudging them towards important information, can be harmful to users with photosensitive epilepsy, who may experience seizures when exposed to content with flashes, transitions to and from saturated red, or repeated patterns. In this paper, we explore three case studies of interactive visualizations created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In SB20,SSB21]). We found no papers that engage vestibular accessibility, such as motion and animation-related accessibility.…”
Section: Research Advancements In Data Visualization and Accessibilitymentioning
confidence: 99%
“…In SB20,SSB21]). We found no papers that engage vestibular accessibility, such as motion and animation-related accessibility.…”
Section: Research Advancements In Data Visualization and Accessibilitymentioning
confidence: 99%
“…The first mention of flicker in the context of photosensitive accessibility for visualizations occurred when Conti et al demonstrated that seizureinducing sequences could be produced by a hypothetical malicious attacker manipulating the data represented in mission-critical visualizations [22]. Similarly, South & Borkin established that seizure-inducing sequences could be produced via interaction alone in web-based visualizations [52]. While both works were valuable in demonstrating the potential for visualizations being inaccessible to people with photosensitivity, neither of the two papers examined in detail how a visualization might be designed to prevent the accidental production of seizure-inducing sequences.…”
Section: Accessible Data Visualizationmentioning
confidence: 99%
“…Prior work has established that data visualizations are capable of producing seizure-inducing sequences as a result of data manipulation [22] and user interaction [52], but to date no systematic work has been conducted to formalize how data visualizations might be inaccessible to those with photosensitivity. In this paper we present our work towards addressing this gap.…”
Section: Introductionmentioning
confidence: 99%
“…All that is truly needed from us is a willingness to use strobing visualizations as mere cosmetic trappings, without regard for their medical ramifications for some viewers. We refer the reader to South et al [72,73], who describe a set of highly usable methods for formulating such attacks.…”
Section: Graphic Violence (Physical Direct)mentioning
confidence: 99%